AN ANALYSIS OF SPEECH FUNCTION IN ENGLISH CLASSROOM INTERACTION OF ENGLISH COURSE AT BALLE VILLAGE KAHU DISTRICT BONE REGENCY - Sitti Aminah; Khaerunnisa; Rahmi; Andi Vivin Vitria (JLE: Journal of Literate of English Education Study Program, 2022)
This study refers to the use of speech functions in English classroom interaction. The writer considers what types of speech function in English classroom interaction are important to be analyzed to know how the speech function is used in mentor-student classroom interaction and to show the most dominant types of speech function used in classroom interaction. The type of research used in this study used a qualitative descriptive approach. The research instruments were observation (non-participant observers) and interviews. The data analysis method used in this study refers to the theory of Miles and Huberman. Based on the results of the research, this study is that by analyzing the speech function used by English mentors during teaching, the researcher found the fact that James Holmes' theory of speech function has 6 namely expressive, directive, referential, metalinguistic, Phatic, and poetic. However, after this research was conducted, not all elements of the speech function were used by English mentors. The researchers could only figure out five of six kinds of speech functions. They are expressive, directive, referential, metalinguistic, and Phatic. So, the researchers found that English mentors were more dominant in using Expressive utterances, which was 36%.